Transformative 3D Printing of Carbon‐metal Nanocomposites as Catalytic Joule Heaters for Enhanced Ammonia Decomposition - Paul Smith; Jiachun Wu; Anthony Griffin; Kaleb Jones; Jeff Aguinaga; Ethan Bounds; Derek Patton; Yizhi Xiang; Zhe Qiang (Advanced Science)
Abstract Electrified thermal chemical synthesis plays a critical role in reducing energy consumption and enabling the industrial decarbonization. While Joule heating offers a promising alternative to gas‐burning furnace systems by directly heating substrates via renewable energy supply, most approaches can only heat the reactor, not the catalytic sites. This limitation stems from the lack of methods to on‐demand create Joule heaters containing in situ loaded catalytic nanoparticles. This work introduces a scalable platform for producing carbonaceous Joule heaters embedded with catalytic nanoparticles from 3D‐printed polypropylene precursors, prepared through crosslinking, metal nitration immersion, and pyrolysis steps. Specifically, sulfonate groups on crosslinked PP can bind with metal ions, yielding well‐dispersed, nanosized particles within a carbon structure that maintains macroscopic dimensional accuracy throughout the manufacturing. The approach is modular, allowing control over particle size and composition. Structured carbon with in situ loaded nickel nanoparticles demonstrates efficient Joule heating, high catalytic activity, and significantly reduced activation energy for catalytic ammonia decomposition. This work provides an innovative material and manufacturing platform to produce structured, catalytically active Joule heaters for decarbonization of chemical synthesis and energy production.